Exploring Effective Physics Teaching Strategies in High Schools during the COVID-19 Pandemic - Roberto Luca Mazzola; Paolo Gondoni; Matteo Bozzi; Juliana Elisa Raffaghelli; Maurizio Zani (MDPI AG, 2023)
The need for educational approaches that comply with the restrictions arising from the COVID-19 pandemic has raised a number of critical issues for students of different age groups. The delicate transition between high school and university has become a key point to focus on, leading many institutions to replan projects dedicated to students involved in this transition. A Physics vocational training project for high school students was carried out in the school year 2020-2021, and it was replicated in the school year 2021-2022. The project included webinars, self-assembled laboratory group experiences, and peer evaluation. The starting point on which we designed our project is that learning is an experience; thus, we built the entire project by particularly focusing on two peculiarities. One peculiarity is the assessment methods: student presentations describing their own experiences were evaluated by teachers and their peers. The second peculiarity is the open approach with respect to how students handle experimental activities. We present a description of these projects along with the results of an evaluation survey filled out by the participants and a descriptive analysis of the assessment strategies. Students appreciated the design of the entire project and, better still, the peer evaluation process. Moreover, we discovered that the evaluation provided by the teachers is lower compared to the assessment reported by the students. This disparity holds potential significance from a statistical perspective and warrants further investigation.